Are microplastics destabilizing the global network of terrestrial and aquatic ecosystem services? - Sridharan, Srinidhi; Kumar, Manish; Bolan, Nanthi S.; Singh, Lal; Kumar, Sunil; Kumar, Rakesh; You, Siming (Environmental research, 2021)
Plastic has created a new man-made ecosystem called plastisphere. The plastic pieces including microplastics (MPs) and nanoplastics (NPs) have emerged as a global concern due to their omnipresence in ecosystems and their ability to interact with the biological systems. Nevertheless, the long-term impacts of MPs on biotic and abiotic resources are not completely understood, and existing evidence suggests that MPs are hazardous to various keystones species of the global biomes. MP-contaminated ecosystems show reduced floral and faunal biomass, productivity, nitrogen cycling, oxygen-generation and carbon sequestration, suggesting that MPs have already started affecting ecological biomes. However, not much is known about the influence of MPs towards the ecosystem services (ESs) cascade and its correlation with the biodiversity loss. MPs are perceived as a menace to the global ecosystems, but their possible impacts on the provisional, regulatory, and socio-economic ESs have not been extensively studied. This review investigates not only the potentiality of MPs to perturb the functioning of terrestrial and aquatic biomes, but also the associated social, ecological and economic repercussions. The possible long-term fluxes in the ES network of terrestrial and aquatic niches are also discussed.